2015
DOI: 10.1637/10927-082914-reg
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Interactions of a Live Infectious Bursal Disease Virus Vaccine for Chickens Based on Strain IBD V877

Abstract: Infectious bursal disease (IBD) is a highly contagious disease in young chickens which can result in high morbidity and mortality and also in great economic losses. The main target for the virus is the lymphoid tissue with a special predilection for the bursa of Fabricius. Several vaccines are available to control the disease. Intermediate plus vaccines are used in chickens with high maternal antibody titers which face high infection pressure. An example of an intermediate plus vaccine is a live vaccine based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Furthermore, in subsequent evaluations after 35 and 42 days, the score showed a tendency to drop to 2.00 and 1.83, clearly demonstrating the regenerative capacity of lymphoid follicles (Table 1 and Figure 5). These results support the use of this V877 strain (GEERLIGS et al, 2015) as a safe vaccine candidate. This regeneration capacity of the lymphoid follicles is related to the integrity of the basement membrane that makes the lining of the follicles where the presence of preserved follicular dendritic cells was observed in the histopathological assessment of vaccinated birds.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, in subsequent evaluations after 35 and 42 days, the score showed a tendency to drop to 2.00 and 1.83, clearly demonstrating the regenerative capacity of lymphoid follicles (Table 1 and Figure 5). These results support the use of this V877 strain (GEERLIGS et al, 2015) as a safe vaccine candidate. This regeneration capacity of the lymphoid follicles is related to the integrity of the basement membrane that makes the lining of the follicles where the presence of preserved follicular dendritic cells was observed in the histopathological assessment of vaccinated birds.…”
Section: Discussionsupporting
confidence: 77%
“…Immunisation of broiler chicks with intermediate or intermediate-plus strains and immunisation of breeders with live attenuated/inactivated vaccines is widely used to control IBDV infection worldwide. However, IBD outbreaks in vaccinated flocks have been documented in several countries (Geerligs et al, 2015). To date, vvIBDV strains have received the most attention because these strains cause acute infection, with high mortality and significant clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the induction of humoral immunity clearly correlated with the induction of bursal lesions and IBDV replication while conventional live IBDV vaccine inflicts transient bursal damage increasing the bursal lesion scores in broiler chickens ( Rautenschlein et al, 2003 ; Geerligs et al., 2015 ). In present study, the bursal lesion scores evaluated in trial 1 and 2 showed numerically lower scores in the MB-1 groups vis-Ă -vis the Icx vaccine and the conventional live vaccine, M.B.…”
Section: Discussionmentioning
confidence: 91%